The risk-adjusted carbon price - Ton S. van den Bremer; Rick van der Ploeg (Center for Economic Studies and ifo Institute (CESifo), 2019)
We use perturbation methods to derive a rule for the optimal risk-adjusted social cost of carbon (SCC) that incorporates the effects of uncertainties associated with climate and the economy from a calibrated DSGE model. We allow for different aversions to risk and intertemporal fluctuations, convex damages, uncertainties in economic growth, atmospheric carbon, climate sensitivity and damages, their correlations, and distributions that are skewed in the longer run to capture long-run climate feedbacks. Our non-certainty-equivalent rule for the SCC incorporates precaution, risk insurance, and climate sensitivity and damage rate hedging effects to deal with future economic and climatic and damage risks.
Keywords: H21; Q51; Q54; 330; precaution; insurance; hedging; economic; climatic and damage uncertainties; skewness; mean reversion; correlated risks; risk aversion; intergenerational inequality aversion; convex damages